Adaptation to Military Life and its Possible Incidence in the Voluntary Desertion of First Semester Students of the Hichamon Company of the EFIM - Miranda-Yanes, Massiel J. (EFIM Ediciones, 2022)
The purpose of this study was to analyze the adaptability to military life in the voluntary desertion of Marine’s Infantry Training School’s Hichamon Company’s first semester aspirants throughout 2019, 2020 and 2021; For this purpose, a series of objectives were established, through them we try to determine whether or not there is a relationship between the aforementioned categories. A mixed correlational methodology was used in which the statistical analysis and semi-structured interview technique were used as a method of collecting and analyzing information. The analysis of the results allowed to determine that 64% of the voluntary withdrawals that occurred in 2019, 2020 and 2021 were directly related to the lack of adaptability to military life, this being an important factor that ultimately leads the aspirants to make the decision not to continue the process of military training that was being carried out at the Marine’s Infantry Training School with the objective of being sub officers of the National Navy.